Effects of mechanical perturbation gait training on gait and balance function in patients with stroke: A pre-post research study. (August 2020) - Mizrachi, Nama; Treger, Iuli; Melzer, Itshak
Highlights: A single training session with "Just Walk" device didn't improve gait a-symmetry. The diagonal angle of the resistance cord resulted in insufficient horizontal force. An improvement was found in the preparation phase of voluntary stepping. Abstract: Patients with stroke (PwS) demonstrate impaired gait and balance, and asymmetric gait, placing them at high risk of falls. We aimed to investigate the effects of a single training session that included mechanical external perturbation which resists forward movement of the paretic leg during its swing phase of walking on gait and balance in PwS. In a pre-post pilot study, gait asymmetry and balance function were assessed in 22 first-event chronic PwS (i.e., unilateral hemiparesis). PwS underwent tests during baseline and one week later, after participating in a single training session that resisted forward stepping during the swing phase of walking with a device secured around the patient's waist and connected diagonally to the patient's foot by a tension cord. Ground reaction forces and center of pressure were sampled during treadmill gait to assess step length asymmetry. Performance-oriented mobility assessment (POMA), a two-minute walk test (2MWT), and the voluntary step execution test were also measured. We found no significant improvement in step length asymmetry. However, POMA scores, as well as voluntary step execution tests improved with a moderate effect size. It seems that applying diagonal resistance force to the swinging leg resulted in insufficient horizontal force. However, the improvement in the preparation phase, i.e., better weight-bearing abilities during the voluntary stepping, may be due to the compression force applied to the lower limb joints thus providing proprioceptive training. This suggests that proprioceptive training may improve gait performance in stroke patients in a very short training period.